2018
DOI: 10.1111/1365-2745.13023
|View full text |Cite
|
Sign up to set email alerts
|

Consumer‐mediated indirect interaction with a native plant lowers the fitness of an invasive competitor

Abstract: Seed dispersal is a primary driver, via propagule pressure, of biological invasions. In animal‐dispersed plants, theory predicts that indirect ecological interactions at the neighbourhood scale may determine landscape‐scale patterns of seed dispersal and predation, and thus invasion. Indirect interactions in seed dispersal may arise between two plant species if shared seed dispersal agents adjust their foraging decisions to the relative frequencies of co‐occurring seeds. We used seed‐tracking experiments and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…Veech ; Dangremond et al ; Norghauer & Newbery ). A few studies revealed that apparent mutualism (Kitzberger et al ; Xiao & Zhang ) and apparent predation (Lichti et al ; Pesendorfer & Koenig ; Bogdziewicz et al ) occur among tree species through seeds by rodents and birds. Moreover, recent studies showed that seed predation and dispersal of a given tree species can be indirectly affected by other sympatric tree species at the neighbourhood scale (Yi et al ; Garzon‐Lopez et al ; Yi & Wang ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Veech ; Dangremond et al ; Norghauer & Newbery ). A few studies revealed that apparent mutualism (Kitzberger et al ; Xiao & Zhang ) and apparent predation (Lichti et al ; Pesendorfer & Koenig ; Bogdziewicz et al ) occur among tree species through seeds by rodents and birds. Moreover, recent studies showed that seed predation and dispersal of a given tree species can be indirectly affected by other sympatric tree species at the neighbourhood scale (Yi et al ; Garzon‐Lopez et al ; Yi & Wang ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies showed that seed predation and dispersal of a given tree species can be indirectly affected by other sympatric tree species at the neighbourhood scale (Yi et al ; Garzon‐Lopez et al ; Yi & Wang ). However, strict assessments of the seed–seed interactions under animal predation and dispersal for a given tree species within or without a neighbourhood have been largely ignored (but see: Albrecht et al ; Xiao & Zhang ; Bogdziewicz et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Bogdziewicz et al. , c). We should also note that seedlings and saplings of both oaks were rather rare on our transects, limiting our power to detect patterns in their distribution.…”
Section: Discussionmentioning
confidence: 97%
“…petraea and with conspecifics in the native range (Bogdziewicz et al. , c). Furthermore, it is less often consumed by rodents than the native oak, but also less readily dispersed by mice ( Apodemus flavicollis ) and jays ( Garrulus glandarius ; Wróbel unpublished manuscript , Myczko et al.…”
Section: Discussionmentioning
confidence: 99%